2006
DOI: 10.1007/s00268-006-0108-3
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Mesh versus Nylon Mosquito Net for Hernia Repair. A Randomized Double‐blind Study in Burkina Faso

Abstract: In situations where superior results of hernia repair depend on the use of a mesh prosthesis but where commercial material is not available or affordable, the use of Nylon mosquito net may be an alternative. Further studies with a larger number of patients and longer follow-up are justified and recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 15 publications
2
71
0
2
Order By: Relevance
“…21,36 Because groin hernia is a very common condition and its repair is one of the most commonly performed surgical procedures worldwide and because the cost of commercial mesh is prohibitive in many low-and middleincome countries, the findings of this study could have broad relevance for the care of these patients. 1,[4][5][6]37 The recurrence rate of 0.7% with low-cost mesh is consistent with recurrence rates reported with commercial mesh in high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…21,36 Because groin hernia is a very common condition and its repair is one of the most commonly performed surgical procedures worldwide and because the cost of commercial mesh is prohibitive in many low-and middleincome countries, the findings of this study could have broad relevance for the care of these patients. 1,[4][5][6]37 The recurrence rate of 0.7% with low-cost mesh is consistent with recurrence rates reported with commercial mesh in high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…(9) The incidence of superficial infection in this series was 2.86% with no deep infection or mesh rejection. In Tongaonkar and B V Reddy's study, the minor infection rate was 4.7 % ( 9) and it was 7% in Brian Stephensons series (5) which also used MNM for hernia repair in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Both clinical and experimental evidence (5) support the use of indigenous MNM to augment the repair of inguinal hernia to achieve results similar to those of commercial meshes. This is a retrospective study evaluating efficacy and cost of MNM as against conventional mesh repair.…”
Section: Introductionmentioning
confidence: 99%
“…2,13,14,15 The clinical effectiveness of this material for hernioplasty is not in doubt. Also in a randomized double blind study in Burkina Faso, Freudenberg S et al 16 had shown that there was no significant difference in the short term clinical outcome of hernia treatment or surgeon's comfort in handling the MNM and the commercial mesh prosthesis.…”
Section: Discussionmentioning
confidence: 99%